Challenges to the implementation of Information technology risk management and compliance in Zimbabwean State Universities - Mupfiga, Paul; Tsokota, Theo; Mamboko, Patrick (The International Journal Of Engineering And Science, 2016)
The paper was purposed at finding the challenges to the implementation of IT risk management and compliance in State universities in Zimbabwe. The existing risk management and compliance processes and frameworks at these universities were assessed. The participants of this research were university councilors, the principal officers, ITS directors and university employees. The research revealed that the culture of risk management is being enforced at universities top levels but there is no communication and training on the launch and implementation of the current risk management frameworks in use at lower levels. It also found out that the IT policies in all the universities were still being drafted and were not yet implemented. The research recommended the implementation and completion of drafting of the IT policies, communication of the IT policies and promotion of the use of the risk frameworks in all university departments, use of flat communication and decision making structures and recommended enforcement of the culture of risk management at low level so as to overcome the challenges to the implementation of IT risk management and compliance.